Penerapan Algoritma C4.5 Untuk Prediksi Keterlambatan Pembayaran Sumbangan Pembinaan Pendidikan (SPP) Santri - Bayu Angkoso; Irmayansyah Irmayansyah (Universitas Binaniaga Indonesia, 2023)
SPP is a mandatory fee for students used by Islamic boarding schools to facilitate all learning activities carried out by students, with a predetermined payment time. One of the problems in paying tuition fees is the case of students being late in paying tuition fees. The problem of late payment of tuition fees is something that must be considered because this can affect the implementation of education and fulfillment of needs and result in a decrease in the financial income of the pesantren. If the problem of late tuition payments can be predicted more quickly, then the management can prevent and anticipate earlier. To overcome this problem, the c4.5 algorithm is applied to predict late payment of tuition fees in order to produce a pattern based on the classification results. By using the variables of Parents' Income, Dependents, Father's Job, First Payment, Second Payment and Third Payment. This is done to see students who have the potential to be late in making tuition payments so that they can anticipate a decline in the financial income of the pesantren. In this study, the accuracy of the c.45 algorithm method has been tested for prediction of late tuition payments using the confusion matrix formula with an accuracy of 76.92%.